Pyruvate dehydrogenase E1α deficiency in a family : Different clinical presentation in two siblings - De Meirleir, L. (1998)
The pyruvate dehydrogenase (PDH) complex (PDHc) is responsible for the irreversible conversion of pyruvate to acetyl-CoA. PDHc is a multienzyme complex consisting of three catalytic subunits, pyruvate decarboxylase (E1), dihydrolipoamideacetyltransferase (E2), dihydrolipoamide dehydrogenase (E3), and two regulatorysubunits, E1 kinase and phospho-E1 phosphatase. An abnormal E1asubunit, whosegene is located on the X chromosome, is the most frequent cause of PDH deÐciency. The clinical presentation of a PDH-E1adeÐciency (McKusick 312170) is variable.We have analysed a family with a mutation (36 bp insertion in exon 10) in thePDH-E1agene in which the male member had a diferent and less severe clinicalpicture than his afected sister.